Large‐Area, Solution‐Processed, Hierarchical MAPbI3 Nanoribbon Arrays for Self‐Powered Flexible Photodetectors. Issue 21 (30th August 2018) - Lim, Seongdong; Ha, Minjeong; Lee, Youngsu; Ko, Hyunhyub
Abstract: Organic–inorganic perovskites with micro‐/nanostructures exhibit outstanding optical and electrical properties, thus attracting increased attention as components of high‐performance optoelectronic devices, but the fabrication of complex micro‐/nanostructured perovskites shows limited success. This study describes the fabrication of hierarchical methylammonium lead iodide (MAPbI3 ) nanoribbon (NR) arrays with controlled internal nanorod structures by simple spin‐coating with solvent treatment process and investigates the suitability of these arrays for high‐performance and multifunctional photodetectors. In the UV‐to‐800‐nm range, photodetectors based on the hierarchical MAPbI3 NR arrays exhibit specific detectivities 18.1–23.7 times higher than those of photodetectors based on MAPbI3 films due to the effective photon management and reduced charge trap states in the hierarchical MAPbI3 NR arrays. The solution‐processed hierarchical MAPbI3 NRs can be fabricated on various substrates including ultrathin polyimide, which facilitates the development of flexible photodetectors with highly stable photoresponse under bending strain. Furthermore, the ferroelectricity and the highly anisotropic alignment of MAPbI3 NR arrays allow multifunctional photodetectors capable of self‐powered and polarization‐sensitive light detection, respectively. The strategy used to fabricate hierarchical organic–inorganic perovskite NR arrays is believed to be applicable to other types of perovskites and can probably be used to construct various optoelectronic devices based on hierarchical nanostructures. Abstract : Hierarchical perovskite nanoribbon arrays with controlled internal nanorod structures are fabricated for high‐performance and flexible photodetectors with enhanced light absorption as well as reduced charge trap states. Furthermore, the ferroelectricity and highly anisotropic alignment of perovskite nanoribbon arrays provide self‐powered and polarization‐sensitive light‐detection capabilities.